Egressos da graduação em Dança-licenciatura da EBA/UFMG e o campo de atuação da educação básica pública em Belo Horizonte e Região Metropolitana - Rayane Nátale Calixto (2023)
This study aimed to analyze the professional field of graduates from the Dance Education undergraduate program at EBA/UFMG in public Basic Education in Belo Horizonte and Metropolitan Region, intending to understand their characteristics and professional context. The goal was to identify challenges and potential pathways for consolidating Dance education in this setting. The research employed a qualitative methodology, utilizing a case study approach with data collected through semi-structured interviews involving seven graduates. The study revealed that the integration of Dance into basic schools in Belo Horizonte and Metropolitan Region remains inconsistent, primarily due to a shortage of qualified professionals in this field. Additionally, political circumstances in Brazil and setbacks in progressive educational efforts aimed at social transformation contribute to these challenges. Persistent issues related to Brazil's Basic Education context and discrepancies concerning Art/Dance as an area of knowledge in schools also play a role. Conversely, the research underscores the significance of the Dance Education program at EBA/UFMG as a crucial formative locus. It prepares professionals dedicated to emancipatory education, emphasizing body knowledge and embodiment, thereby contributing to the integration and consolidation of Dance in schools across Belo Horizonte and Metropolitan Region.